2020
DOI: 10.1016/j.foodchem.2019.125327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tomato (Solanum lycopersicum L.) lycopene-rich extract on the kinetics of rancidity and shelf-life of linseed (Linum usitatissimum L.) oil

Abstract: Effect of tomato (Solanum lycopersicum L.) lycopene-rich extract on the kinetics of rancidity and shelf-life of linseed (Linum usitatissimum L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 36 publications
7
31
2
2
Order By: Relevance
“…This indicated that the oil was slightly dark with the presence of yellow and, in lower degree, green compounds that likely correspond to pigments such as carotenoids and chlorophylls, respectively. The GSO coordinates in the CIELab system were lower than those reported for other oils, such as chia (Ixtaina et al, 2011), pistachio (Ling et al, 2016), and linseed (Varas Condori et al, 2020).…”
Section: Ugartecontrasting
confidence: 64%
“…This indicated that the oil was slightly dark with the presence of yellow and, in lower degree, green compounds that likely correspond to pigments such as carotenoids and chlorophylls, respectively. The GSO coordinates in the CIELab system were lower than those reported for other oils, such as chia (Ixtaina et al, 2011), pistachio (Ling et al, 2016), and linseed (Varas Condori et al, 2020).…”
Section: Ugartecontrasting
confidence: 64%
“…The amount of these unsaturated fatty acids was 84.602 AE 0.554 g/100 g, indicating basil seed oil has a high nutritional value. The composition of fatty acids in basil seed oil was similar to flaxseed oil (Varas Condori et al, 2020), perilla oil (Torri et al, 2019) and Paeonia species oil (Yu et al, 2016). Excitingly, this study detected and identified seven fatty acids (C16:1-9c, C17:0, C18:1-11c, C20:0, C20:1-8c, C22:0 and C24:0) in fresh basil seed oil for the first time compared to a previous study (Mostafavi et al, 2019).…”
Section: Fatty Acid Composition Of Fresh Basil Seed Oilsupporting
confidence: 59%
“…Lyc, a kind of carotenoid, is a popular food ingredient drug at present. Its anti-inflammatory, anticancer, and antioxidative effects in vivo and in vitro have been reported in many articles (Olson and Krinsky, 1995;Condori et al, 2020). In addition, in the daily diet, a large part of Lyc comes from tomatoes, watermelons, pink grapefruit, and other red vegetables or fruits (Islamian and FIGURE 6 | Treatment with Lycopene (Lyc) alleviated oxygen-glucose deprivation (OGD)-induced apoptosis in primary cortical neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Lycopene (Lyc) is a member of the carotenoids family (Olson and Krinsky, 1995;Condori et al, 2020), mainly exists in fruits and vegetables including tomatoes, watermelon, and red pomelo (Mangels et al, 1993). Lyc is especially high in the red variety of tomatoes, and the structure remains in food processing.…”
Section: Introductionmentioning
confidence: 99%